Sustaining an Innovative Culture for Competitive Advantage: Strategic Recommendations for Shopee - Kok Ban Teoh; Changxiang Zou; Haokai Zou; Xixian Li; Tong Zhang; Aellysya Qistina Rizal Djunaidy; Daisy Mui Hung Kee (Journal of The Community Development in Asia, 2026)
Malaysia’s digital economy is growing rapidly, and e-commerce platforms such as Shopee Malaysia must sustain continuous innovation to remain competitive. However, maintaining an innovative culture in a fast-changing environment remains challenging. This study examines how leadership support, employee collaboration and knowledge sharing contribute to sustaining innovation culture and strengthening Shopee’s long-term competitiveness. Using secondary data from annual reports, credible online business sources and academic publications from 2020 to 2024, the study applies descriptive and content-based analysis to identify key patterns and insights. The findings show a steady increase in Shopee’s disclosed indicators related to leadership support and employee collaboration between 2020 and 2024, highlighting a growing emphasis on strategic direction and cross-functional coordination. In contrast, the formal knowledge-sharing mechanisms seem limited, suggesting that knowledge exchange mainly relies on informal cooperation. Based on these insights, the study proposes strategic recommendations to enhance innovation capability and organizational resilience for Shopee and other e-commerce firms seeking lasting competitive advantage.